PENGARUH TOTAL QUALITY SERVICE DAN KEPUASAN PASIEN TERHADAP KINERJA PEGAWAI RSUD LASINRANG KABUPATEN PINRANG - Annisa Mutasari, Nur; Wahyudi; Awaluddin, Awaluddin (Study of Scientific and Behavioral Management, 2025)
This study aims to determine the Influence of Total Quality Service and Patient Satisfaction on the Performance of Employees at Lasinrang Hospital, Pinrang Regency. This study uses a quantitative method with a causal associative approach. The population of this study were patients who had visited Lasinrang Hospital more than once with a sample of 94 respondents, obtained through a purposive sampling method. Data collection was carried out by distributing questionnaires with a Likert scale. The data analysis techniques used were validity, reliability, normality, and multiple regression tests. With data management using SPSS version 22. The results of the study showed that service quality had a positive and significant effect on employee performance, patient satisfaction had a positive and significant effect on employee performance. Based on the results of the study, it is recommended for the management of Lasinrang Hospital to continue to improve the quality of service and patient satisfaction in order to support improved employee performance, which in turn can improve the quality of hospital services as a whole. Keywords: service quality, patient satisfaction, employee performance, Lasinrang Hospital